Presenting a Population-based Multiple Sclerosis Registry for Iran - Emami, Hassan; Asadi, Farkhondeh; Moghaddasi, Hamid; Ghalaneh, Sara (Archives of Advances in Biosciences, 2019)
Introduction: Worldwide prevalence of Multiple Sclerosis (MS) is growing, and given the huge burden on the patient, the community and the healthcare system, prevention interventions and symptom management in order to improving the quality of life of these patients are of utmost importance. One of the most important strategies in this regard is providing the existence of an MS population-based registry. Accordingly, this research was aimed at providing a population-based MS registry model. Materials and Methods: This is a qualitative study, carried out within the years 2016 and 2017. The population of the present study consisted of models of multiple sclerosis population registries. In this study, a model was provided using library resources, informational networks and information retrieval from databases of PubMed, Google Scholar, Springer, Science direct, and Wiley and also through studying the registry of developed countries. Then, this model using Delphi technique and questionnaire tool was validated and after data analysis, the final model was presented. Results: In the present study, a demographic MS registry model including the following eight main criteria was proposed: registry goals, data sources, minimum data set, data set, data processing, various types of reports, quality control measures and patient follow-up procedures. Conclusion: Considering the prevalence of MS in Iran and the need for optimal data management, it is recommended that measures be taken to establish and use a national MS population-based registry and be one of the priorities of the Ministry of Health and Medical Education.